Leadership and staff organizational citizenship behaviour in higher education institutions: A quantitative analysis - Adewale, Adebayo Saheed; Ghavifekr, Simin; Megat Daud, Megat Ahmad Kamaluddin (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
Higher education institutions are known for producing skilled manpower needed to attain sustainable and holistic development. These institutions cannot achieve their predetermined goals without effective leadership. Leadership is an important factor in an organization. Academic leaders are pivot of change in any higher education institution. As a change agent, the success and failure of the system depend on academic leaders. Their belief and judgment about themselves, attitude towards change and policy tell in every aspect of education system. Therefore, this study examined the impact of leadership self-efficacy and change oriented behaviour on staff organizational citizenship behaviour in higher education institutions. It adopted a quantitative research design. A questionnaire consisting of 40 items was used to gather information from 420 respondents who were randomly selected across 10 different public higher education institutions in Lagos State, Nigeria. Structural Equation Modelling(SEM) was used in analysing the data collected in this study. The findings show that leadership self-efficacy, change oriented behaviour and change policy impact significantly on staff organizational citizenship behaviour. In order to improve staff organizational citizenship behaviour and performance in higher education institutions, academic leaders must display a high self-efficacy, be open to innovation, ensure effective communication and adopt friendly policy that will stimulate staff. If all these are put in place, higher education institutions will be able to achieve their set goals and respond positively to the needs of different stakeholders.